Synthesis, Characterization and Crystal Structure of trans-2-(2-Hydroxyphenyl)-1-nitroethylene - Liu, Yun-Feng; Liu, Sheng-Nan; Zhao, Pei-Hua; Li, Xin-Hang; Liang, Wen-Jun; Liu, Ya-Qing (Asian Journal of Chemistry, 2014)
The nitroalkene compound, namely trans-2-(2-hydroxyphenyl)-1-nitroethylene (I), has been successfully synthesized from the condensation of 2-hydroxybenzaladehyde with nitromethane. It was characterized by elemental analysis, 1H NMR spectrum and single-crystal X-ray diffraction analysis. Compound (I) crystallizes in the triclinic, space group P-1 with a = 5.2270(5), b = 11.2130(10), c = 13.6080(13) Å, a = 71.224(18), b = 84.47(3), g = 81.20(3)°, V = 745.29(16) Å3, Z = 4, C8H7NO3, Mr = 165.15, Dc = 1.472 g/cm3, F(000) = 344, μ(MoKa) = 0.115 mm-1, the final R1 = 0.0500 and wR2 = 0.1358 for 2309 observed reflections [I > 2s(I)]. Moreover, the crystal structure of (I) is stabilized by the intermolecular O-H···O hydrogen bonds, the p-p stacking interactions and the C-H···O short contacts, which extend the molecules into an infinite three-dimensional network.